Endogenous opioid systems alterations in pain and opioid use disorder - Higginbotham, Jessica A.; Markovic, Tamara; Massaly, Nicolas; Morón, Jose A. (Frontiers in Systems Neuroscience, 2022)
Decades of research advances have established a central role for endogenous opioid systems in regulating reward processing, mood, motivation, learning and memory, gastrointestinal function, and pain relief. Endogenous opioid systems are present ubiquitously throughout the central and peripheral nervous system. They are composed of four families, namely the µ (MOPR), κ (KOPR), δ (DOPR) and nociceptin/orphanin FQ (NOPR) opioid receptors systems. These receptors signal through the action of their endogenous opioid peptides β-endorphins, dynorphins, enkephalins and nociceptins, respectfully, to maintain homeostasis under normal physiological states. Due to their prominent role in pain regulation, exogenous opioids - primarily targeting the MOPR, have been historically used in medicine as analgesics, but their ability to produce euphoric effects also present high risks for abuse. The ability of pain and opioid use to perturb endogenous opioid system function, particularly within the central nervous system, may increase the likelihood of developing opioid use disorder (OUD). Today, the opioid crisis represents a major social, economic, and public health concern. In this review, we summarize the current state of the literature on the function, expression, pharmacology, and regulation of endogenous opioid systems in pain. Additionally, we discuss the adaptations in the endogenous opioid systems upon use of exogenous opioids which contribute to the development of OUD. Finally, we describe the intricate relationship between pain, endogenous opioid systems, and the proclivity for opioid misuse, as well as potential advances in generating safer and more efficient pain therapies.